The turistic heritage, economic activities linked to ecotourism and its relation to vulnerability to climate change in the municipalities of the Huasteca Potosina - Segura Mojica, Francisco Javier (2021)
The objective of this research was to identify and estimate the statistical relationship that exists between the ecotourism potential, the economic activities linked to tourism, such as the offer of accommodation and food and drink services, and vulnerability to climate change. in the municipalities of the Huasteca Potosina area. Data were obtained corresponding to the natural and cultural tourism index by municipality, the number of temporary accommodation establishments and food and beverages, as well as the vulnerability index to climate change for each of the eighteen municipalities in the area. Subsequently, the Pearson correlation indexes were calculated among the aforementioned variables, finding statistically significant relationships between the tourist offer and climate vulnerability.